52 INTEROPERABILITY OF COMMAND TROOPS WITH COMBAT AIRCRAFT AND HELICOPTER PERSONNEL IN SUPPORTING COMBAT S EARCH AND RESCUE OPERATIONS (Strategi Pertahanan Udara, 2022)
The interoperability of the Paskhas (Indonesian Airforce Special Troops) Combat SAR (CSAR) Team with elements of RESCAP and RESCORT combat aircraft and CSAR helicopters is very much needed in the implementation of Combat SAR Operations. However, exercises are rarely carried out with the dynamics of actual and complex Combat SAR operation scenarios, at this time the exercises are only limited to demonstrations of Combat SAR operations. The current problems are the lack of Ground Forward Air Control (GFAC) capability of the Combat SAR (CSAR) team, the lack of training with aircraft elements, special equipment and limited infrastructure, and the absence of software to support the creation of Interoperability of the Paskhas Combat SAR (CSAR) Team with elements of fighter aircraft and helicopters. The purpose of this study was to analyze the existing and ideal conditions of interoperability of the Combat SAR Paskhas team with the crew of RESCAP, RESCORT and CSAR helicopters to support Combat SAR operations and the efforts made to overcome these interoperability constraints. The method used is qualitative. The results of the discussion of this study are that the interoperability of the Paskhas Combat SAR (CSAR) Team with elements of RESCAP fighter aircraft, RESCORT fighter elements, and CSAR helicopter elements is not optimally.Keywords: Interoperability, Capability, Paskhas (Indonesian Airforce Special Troops), Combat SAR Operations